PEMANFAATAN KEARIFAN LOKAL DALAM PEMBELAJARAN EKONOMI UNTUK MENINGKATKAN RELEVANSI KURIKULUM - Laia, Baziduhu (LPPM Universitas Nias Raya, 2024)
This study aims to examine the utilization of local wisdom in economic education in Nias and its impact on curriculum relevance. The local wisdom in Nias, which includes traditional economic practices, barter systems, and natural resource management, has significant potential to enhance students' understanding of economic concepts. Using a qualitative approach, this research analyzes various literature sources and case studies to identify how local wisdom can be integrated into the educational curriculum. The findings indicate that the utilization of local wisdom not only increases student interest and engagement but also strengthens cultural identity and character development. Furthermore, the study identifies implementation challenges that need to be addressed to achieve these goals. It is hoped that this research can contribute to the development of a more relevant and contextual curriculum for students in Nias.